2011
DOI: 10.1007/s13555-011-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Erosive lichen planus of the soles: Effective response to prednisone

Abstract: BackgroundErosive lichen planus (LP) of the soles is a rare variant of LP, characterized by chronic, painful, and disabling plantar ulcerations. Herein, we report a case with complete healing following treatment with systemic steroids.Case reportA 38-year-old woman was referred with painful and disabling erosive bilateral plantar LP, which she had experienced for 6 weeks. A 1 mg/kg/day, oral prednisone therapy led to rapid improvement and complete healing within 3 weeks, with a sustained result under a low dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Oral lichen planus is often ulcerative [ 12 ]. Treatment of ulcerative plantar lichen planus needs systemic immunosuppression and often surgery [ 13 ][ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral lichen planus is often ulcerative [ 12 ]. Treatment of ulcerative plantar lichen planus needs systemic immunosuppression and often surgery [ 13 ][ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Actually, variants of palmoplantar LP, with other clinical manifestations of LP may appear contemporaneously in an individual. [3][4][5]9,15,16 There are case reports indicating hyperkeratotic palmoplantar plaques accompanying oral manifestations and typical cutaneous lesions of LP. 4,15 Likewise, plantar ulcero-erosive lesions of LP have been described with longitudinal melanonychia, reticular oral LP, and post inflammatory hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…4,15 Likewise, plantar ulcero-erosive lesions of LP have been described with longitudinal melanonychia, reticular oral LP, and post inflammatory hyperpigmentation. 9,16 Up to date the most comprehensive investigation regarding palmoplantar LP has been held by Sanchez-Peres et al 5 Although it can't be figured out which combinations of clinical presentations their patients had displayed, they reported that simultaneous appearance rate of LP in the palmoplantar region and elsewhere was 26%. In this study the palmoplantar lesions were classified according to prevailing morphological patterns, as the erythematous scaly variant was the most common type observed, occurring in three-quarters of the patients, and the hyperkeratotic pattern was the second most prevalent one, described in the remaining one-quarter.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date 10 cases have been described [27,28,29,30,31,32,33,34,35]. Erosive LP is a painful variant of LP with eroded or ulcerated lesions mainly in mucocutaneous sites which is often difficult to treat and may lead to scarring [36,37,38]. Lichen planus pemphigoides refers to a cross-over syndrome of LP and bullous pemphigoid [5] and associations with drug intake have been described (PUVA [39], UVB, paracetamol or ibuprofen [40], simvastatin [41] and ramipril [42,43]).…”
Section: Discussionmentioning
confidence: 99%